Comparison of Turbulence Models for the Prediction of Hydrodynamics of Packed Beds under Supercritical Fluid Condition - Malang, Jameson (Curtin University, 2017)
The rate of transfer processes in packed bed is governed by the hydrodynamics of the bed. Therefore, the study of fluid flow within the bed using suitable turbulence model is crucial. This comparative study of four turbulence models (standard k-ε, RNG k-ε, realizable k¬-ε and SST k¬-ω) was performed for subcritical and supercritical regimes. The results of the predicted hydrodynamics were presented in detail and SST k¬-ω turbulence model is recommended for single sphere simulation.